Computed tomographic findings in dogs with suspected aspiration pneumonia: 38 cases (2014‐2019). (25th November 2022) - Constantinescu, R.; Istrate, A.; Sumping, J. C.; Dye, C.; Schiborra, F.; Mortier, J. R.
Abstract : Objectives: To describe computed tomographic (CT) findings in dogs diagnosed with aspiration pneumonia and to assess for any correlation with patient outcome. Materials and Methods: Retrospective analysis of 38 cases with a presumptive diagnosis of aspiration pneumonia at two UK referral centres. Medical records were reviewed for signalment, history, physical examination and clinicopathologic data. CT examinations of the thorax were reviewed by the European College of Veterinary Diagnostic Imaging board‐certified radiologist for all dogs to describe the characteristics and distribution of the pulmonary lesions. Results: The most common CT findings were lung lobe consolidation associated with air bronchograms (100%) followed by ground‐glass attenuation (89.4%), bronchial wall thickening (36.8%), bronchiolectasis (31.5%) and bronchiectasis (15.7%). Large‐breed dogs were overrepresented. Duration of hospitalisation ranged between 0 and 8 days (mean 3 days). Overall, 89.4% of dogs survived the aspiration event and were discharged from the hospital. The four dogs that did not survive to discharge had five or more lobes affected on CT. Clinical Significance: CT findings in dogs with aspiration pneumonia are described. CT is a useful imaging modality to diagnose aspiration pneumonia.